Mitigating Power Quality Issues: A Study on STATCOM and UPQC with Enhanced Control Methods - Kumar Yegireddy, Narendra; Santosh Kumar, Gottapu; Kumar, M N V S S; Rajesh, Budumuru (International Journal of Psychosocial Rehabilitation, 2020)
In both commercial and industrial settings, power systems incorporate a diverse array of electrical, electronic, and power electronic equipment. The quality of electrical power in such systems can be significantly impacted by various factors, including harmonic distortion stemming from non-linear loads like thyristor power converters and rectifiers. Additionally, issues like voltage and current flickering due to equipment such as arc furnaces, as well as voltage sag and swell caused by switching loads, can adversely affect the reliable supply of power to sensitive loads. To address these challenges, the Unified Power Quality Conditioner (UPQC) emerges as a custom power device. It comprises shunt and series converters connected in a back-to-back configuration on the DC side, effectively addressing load current and supply-voltage imperfections. The performance of a UPQC system critically hinges on the accuracy and rapidity with which reference signals are derived. In this paper, we present a designed UPQC model featuring a DC link for shunt and series compensation. This design offers the advantage of reducing the likelihood of simultaneous converter malfunction. To optimize UPQC operation, distinct control strategies are developed for the shunt and series converters. The shunt compensation and series compensation within the UPQC model are each realized through the implementation of distinct control methods. Specifically, we employ a Proportional-Integral (PI) controller for shunt compensation, while a hysteresis controller is utilized for series compensation. The hysteresis current control strategy is tailored to maintain harmonic levels below 5 percent, thereby ensuring improved power quality and the reliable operation of sensitive equipment in commercial and industrial settings.